PECULIARITIES OF USING THE PARTICIPATORY APPROACH IN HIGHER EDUCATION IN THE UNITED STATES AND THE UNITED KINGDOM - Zhukov, Vasyl (Scientific notes of the pedagogical department, 2025)
The main task of modern higher education is to teach students to create, search, share experiences, and implement best practices in the content of education. The innovations of the higher education system today include the ideas of human centredness, student-centred learning based on a participatory approach. It has been established that at the present stage, this approach is widespread in higher education institutions of the USA and the UK. Therefore, generalisation and creative use of the practices of leading universities in the United States of America and the United Kingdom can provide significant assistance in applying the participatory approach in higher education institutions of Ukraine. The purpose of the article is to clarify the peculiarities of using the participatory approach in higher education in the United States of America and the United Kingdom, which is aimed at improving interpersonal relations, promoting cooperation between teachers and students, serving as the basis for successful communication during classes and providing an opportunity for active participation of each student in the learning process.The study shows that the peculiarities of using the participatory approach in higher education in the United States and the United Kingdom include: the introduction of ‘open curricula’ by universities; joint creation of the course curriculum by both teachers and students; development of research programmes for undergraduate and graduate students; introduction of practical training programmes; active participat ion of students in discussions, group projects and extracurricular activities; widespread introduction of reading and self-study practices; creation of a virtual environment; introduction of interdisciplinary courses and various forms and methods of formal and summative assessment; self-assessment of students’ own activities; active participation of students in the assessment of teaching and learning; providing each student with a ‘personal teacher’; organisation of student-centred learning; wide involvement of multimedia tools, digital resources and online platforms in the learning process; creation of a flexible learning environment; fostering creative thinking of students.